A comparison of realised measures for daily REIT volatility. Issue 1 (2nd January 2020) - Zhou, Jian
ABSTRACT: Recent advances in financial econometrics have led to the development of a variety of estimators of asset volatility using frequently sampled price data, known as 'realised measures'. These estimators rely on different assumptions and take many different functional forms. In this paper, we aim to examine the accuracy of these estimators in the measurement of daily volatility of REIT returns. We consider a wide range of commonly used realised measures and apply them to several major global REIT markets. Our findings suggest that there is no single estimator which can perform the best for all markets under study. The best-performing estimator varies across markets. We obtain our results by considering the accuracy of both volatility estimation and forecast and by using multiple robust evaluation metrics.